"Your Body Is Not At All Where You Left It": Adolescent and Young Adult Cancer Survivors' Experiences Transitioning Back Into Physical Activity After Treatment. (May 2022) - Vani, Madison F.; Sabiston, Catherine M.; Santa Mina, Daniel; Trinh, Linda
Physical activity (PA) can help manage cancer treatment-related side effects and improve well-being following treatment; however, resuming PA after a period of inactivity due to cancer can be challenging. The purpose of this study was to explore adolescents and young adults (AYAs) experiences transitioning back into PA after a period of inactivity due to cancer treatment. Twelve previously active AYAs ( M age = 30 ± 5.8 years) were purposefully sampled and engaged in a semi-structured interview. The following four themes were generated through a reflexive thematic analysis: PA is described as important and valuable; navigating one's appearance and fitness changes after cancer treatment within the PA context; supportive care is essential to successful PA transitions; and juxtaposed environments: fitness facilities, cities, and green spaces. Developing strategies aimed at gradually transitioning into PA should be a priority to improve AYAs' well-being through survivorship.